Lighthouse keeper's catastrophe - Armitage, Ronda; Armitage, David (London : Puffin, 1988)
After Mr. Grinling, the lighthouse keeper loses his key to the lighthouse door, Mrs. Gringling comes up with a plan to get Mr Gringling back into the lighthouse.
Keywords: Lighthouse keepers -- Fiction